Sorcery in Mesoamerica - Coltman, Jeremy D., editor; Pohl, John M. D., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2021)
Examines and reconstructs the original indigenous logic behind sorcery, analyzing manifestations from the early Olmec to the ethnographic present. While the topic of sorcery and witchcraft in anthropology is well developed in other areas of the world, it has received little academic attention in Mexico and Central America region until now.--Provided by publisher.
Sorcery and witchcraft in the Mesoamerican world: an introduction / John M.D. Pohl and Jeremy D. Coltman -- Spanish taxonomies of witchcraft and the colonial highland Maya / John Monaghan -- Sorcery and counter-sorcery among the Nahua of Northern Veracruz, Mexico / Alan R. Sandstrom and Pamela Effrein Sandstrom -- Witchcraft in a Mixtec and Tlapanec municipality of the Costa Chica of Guerrero: a sociocultural epidemiology / Lilián González Chévez -- Ah Mak Ikob yetel Ah Pul Yahob: Yucatec Maya witchcraft and sorcery and the Mestizaje of magic and medicine in colonial Yucatán, 1570-1790 / John F. Chuchiak IV -- The jaguar's line: witchcraft and sorcery in Mesoamerica / Timothy J. Knab -- The ways of witchcraft: sorcery and political power among the Classic Maya / David Stuart -- Where children are born: centipedes and feminine sexuality in Ancient Mesoamerica / Oswaldo Chinchilla Mazariegos -- "The Devil Incarnate": a comparative perspective on 'Deer-Serpents' in Mesoamerican beliefs and ritual practices / Jesper Nielsen -- The sorcerer's cosmos: reconstructing Codex Aubin 20 / John M.D. Pohl -- Nahua sorcery and the classic Maya antecedents of the Macuiltonaleque / Jeremy D. Coltman -- From clay to stone: the demonization of the Aztec goddess Cihuacoatl / Cecelia F. Klein -- Nahualli ihuan tlamacazqui: witches, sorcerers and priests in Ancient Mexico / Roberto Martínez González.
Copyright date is 2021.
Keywords: Witchcraft -- Mexico; Witchcraft -- Central America; Mayas -- Social life and customs; Indians of Mexico -- Social life and customs; Indians of Central America -- Social life and customs